Performance and fault analysis of Telekom Malaysia IPLC (International Private Leased Circuit) / Wan Mohd Zaid Wan Md Ali - Wan Md Ali, Wan Mohd Zaid (2006)
In information technology age today, Businesses are done without physical presence it can be carried out remotely. These are possible for constant growth of International Network infrastructure surrounded the Globe. Multinational firms able to locate their plants in almost anywhere they liked. They can operate efficiently even though offices are thousand miles away from home. Without physical outlet they can virtually sell the product event customizing their product manufacturing as what implemented by DELL cooperation. The world class Telecommunication Company like SingTel is also placed their Helpdesk outside of their soil for economical workforce. All these are possible due to IPLC existence to serve their needs. This Independent Study is discussed on IPLC performance and fault analysis in the scope of Telekom Malaysia topography. There was a study conducted by undergraduate student pertaining to ATM performance analysis which looking at detail throughput and stability of UITM Coins Network. His thesis for first degree is deep touch on switched network which investigate all individual PVC in ATM and touched little bit on local access (Local Leased Line). The Local Access is part of IPLC component in my Independent study. The study is very important in determining the reasons of why IPLC performance is degraded and what cause of degradation. By taking actual scenario of IPLC as an empirical study, we examined the performance parameters G.821 ITU recommendation and evaluate for the findings. The one year fault activity report is translated into meaningful graph of service availability and fault distribution performance parameters. For the unstable scenario we took IPLC to Pakistan as an example to detail study root cause. From the finding we come up with the recommendations for improvement.